2018
DOI: 10.1007/s11605-017-3660-2
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Incidence of Pancreatic Fistula After Pancreaticoduodenectomy and the Degree of Pancreatic Fibrosis

Abstract: ObjectiveThe objective of this study is to investigate the association between the incidence of pancreatic fistula after pancreaticoduodenectomy (PD) and the degree of pancreatic fibrosis.MethodBetween January 2013 and December 2016, the analysis of the clinical data of 529 cases of pancreaticoduodenectomy patients of our hospital was performed in a retrospective fashion. The univariate analysis and multivariate analysis were done using the Pearson chi-squared test and binary logistic regression analysis model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 18 publications
2
37
0
6
Order By: Relevance
“…The pancreatic duct size has been reported as an independent risk factor for POPF . It could be measured at the presumed surgical pancreatic margin or by preoperative CT scan.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The pancreatic duct size has been reported as an independent risk factor for POPF . It could be measured at the presumed surgical pancreatic margin or by preoperative CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al suggested that the degree of pancreatic fibrosis is a prognostic factor which influences the pancreatic texture and the incidence of POPF. 16 The pancreatic CT value was used as a quantitative index for calculating the pancreatic fibrosis score to predict the incidence of POPF. Mathur et al revealed that patients with POPF presented decreased pancreatic fibrosis score (<2%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations